Investasi dalam Perspektif Islam - Rizki, Nabila Nurul (PT Literasi Nusantara Publisher, 2023)
Investment is an investment activity that is used to increase income or obtain a number of benefits in the future. Investment activities are highly recommended in Islam, because investment can make a major contribution to society if used productively. This is stated in various verses in the Qur'an. However, not all investments are allowed in Islam, there are limits set in making investments, where the investment made must be in the halal sector, not containing usury, gambling, speculation, and does not contain elements of gharar and maisyir.